Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 51834 by Abdo msup. last updated on 31/Dec/18

calculatef(a)= ∫_0 ^∞   ((ln(1+at^2 ))/(1+t^4 ))dt  with a>0.  2)find the value of ∫_0 ^∞    ((ln(3+t^2 ))/(1+t^4 ))dt.

calculatef(a)=0ln(1+at2)1+t4dtwitha>0. 2)findthevalueof0ln(3+t2)1+t4dt.

Commented byAbdo msup. last updated on 31/Dec/18

1) we have f^′ (a)= ∫_0 ^∞    (t^2 /((1+at^2 )(t^4 +1)))dt  =(1/2) ∫_(−∞) ^(+∞)    (t^2 /((at^2  +1)(t^4  +1)))dt  let   ϕ(z)=(z^2 /((az^2  +1)(z^(4 ) +1)))  we have   ϕ(z)= (z^2 /(((√a)z−i)((√a)z +i)(z^2 −i)(z^2  +i)))  =(z^2 /(a(z−(i/(√a)))(z+(i/(√a)))(z−e^((iπ)/4) )(z+e^((iπ)/4) )(z−e^(−((iπ)/4)) )(z+e^(−((iπ)/4)) )))  the poles of ϕ are +^−   (i/(√a))  and +^−  e^((iπ)/4)   and +^−  e^(−((iπ)/4))   (all simples)  residus tbeorem give  ∫_(−∞) ^(+∞)   ϕ(z)dz =2iπ{ Res(ϕ,(i/(√a)))+Res(ϕ,e^((iπ)/4) )+Res(ϕ,−e^(−((iπ)/4)) )}  Res(ϕ, (i/(√a))) =((−1)/(a^2 ((2i)/(√a))((1/a^2 )+1))) =((−(√a))/(2i(1+a^2 ))) =((i(√a))/(2(1+a^2 )))  Res(ϕ,e^((iπ)/4) ) =(i/((ai+1)(2e^((iπ)/4) )(2i))) = (e^(−((iπ)/4)) /(4(1+ai)))  Res(ϕ,−e^(−((iπ)/4)) ) = ((−i)/((1−ai)(−2e^(−((iπ)/4)) )(−2i)))  = −(e^((iπ)/4) /(4(1−ai))) ⇒  ∫_(−∞) ^(+∞)  ϕ(z)dz =2iπ{ ((i(√a))/(2(1+a^2 ))) −(1/4)(2iIm( (e^((iπ)/4) /(1−ai)))}  =((−π(√a))/(1+a^2 )) −π Im((e^((iπ)/4) /(1−ai)))  but  (e^((iπ)/4) /(1−ai)) = ((e^((iπ)/4) (1+ai))/(1+a^2 )) = ((((1/(√2))+(i/(√2)))(1+ai))/(1+a^2 ))  =(1/(√2)) (((1+i)(1+ai))/(1+a^2 )) =((1+ai+i−a)/((√2)(1+a^2 ))) =((1−a +i(1+a))/((√2)(1+a^2 ))) ⇒  ∫_(−∞) ^(+∞)  ϕ(z)dz = ((−π(√a))/(1+a^2 )) −π ((1+a)/((√2)(1+a^2 ))) ⇒  f^′ (a) = ((−π(√a))/(2(1+a^2 ))) −((π(1+a))/(2(√2)(1+a^2 ))) ⇒  f(a) =−(π/2) ∫   (((√a) da)/(1+a^2 )) −(π/(2(√2))) ∫  ((1+a)/(1+a^2 )) da +c

1)wehavef(a)=0t2(1+at2)(t4+1)dt =12+t2(at2+1)(t4+1)dtlet φ(z)=z2(az2+1)(z4+1)wehave φ(z)=z2(azi)(az+i)(z2i)(z2+i) =z2a(zia)(z+ia)(zeiπ4)(z+eiπ4)(zeiπ4)(z+eiπ4) thepolesofφare+iaand+eiπ4and+eiπ4(allsimples) residustbeoremgive +φ(z)dz=2iπ{Res(φ,ia)+Res(φ,eiπ4)+Res(φ,eiπ4)} Res(φ,ia)=1a22ia(1a2+1)=a2i(1+a2)=ia2(1+a2) Res(φ,eiπ4)=i(ai+1)(2eiπ4)(2i)=eiπ44(1+ai) Res(φ,eiπ4)=i(1ai)(2eiπ4)(2i) =eiπ44(1ai) +φ(z)dz=2iπ{ia2(1+a2)14(2iIm(eiπ41ai)} =πa1+a2πIm(eiπ41ai)but eiπ41ai=eiπ4(1+ai)1+a2=(12+i2)(1+ai)1+a2 =12(1+i)(1+ai)1+a2=1+ai+ia2(1+a2)=1a+i(1+a)2(1+a2) +φ(z)dz=πa1+a2π1+a2(1+a2) f(a)=πa2(1+a2)π(1+a)22(1+a2) f(a)=π2ada1+a2π221+a1+a2da+c

Terms of Service

Privacy Policy

Contact: info@tinkutara.com